A Systematic Review and Pooled Analysis of Select Safety Parameters Among Normal Healthy Volunteers Taking Placebo in Phase 1 Clinical Trials. (16th May 2017) - Young, Tina C.; Srinivasan, Subasree; Vetter, Marion L.; Sethuraman, Venkat; Bhagwagar, Zubin; Zwirtes, Ricardo; Narasimhan, Premkumar; Chuang, Tilda; Smyth, Brendan J.
Abstract: A systematic review of the Bristol‐Myers Squibb normal healthy volunteers (NHVs) database identified phase 1 trials that included NHVs administered placebo with the aim of characterizing normal inter‐ and intraindividual safety parameter variability. Twenty‐five single and multiple ascending dose studies, median duration 28 (2 to 63) days, were included in the pooled analysis (355 NHVs). Laboratory evaluations, vital signs, electrocardiograms, and adverse events were assessed. The most commonly occurring adverse event was headache (28 [7.9%] NHVs; 519.5 events/100 person‐years). During the dosing period (on placebo), evaluations showed 5.1 events/100 measures of alanine aminotransferase and 7.3 events/100 measures of creatine kinase 1× above the upper limit of normal. Alanine aminotransferase and creatine kinase elevations occurred in 28 (7.9%) and 39 (11.0%) NHVs, respectively; 105 (30.3%) NHVs had low and 46 (13.3%) had high diastolic blood pressure. This analysis may inform future study designs and provide a context for interpretation of safety signals in early phase clinical trials.